Fabrication and characterization of electrospun fish gelatin mats doped with essential oils and β-cyclodextrins for food packaging applications - Mahmood, Kaiser; Kamilah, Hanisah; Karim, Alias A.; Ariffin, Fazilah (Springer, 2022)
The extensive and alarming use of non-renewable synthetic plastics and artificial additives in food packaging is urging to design biodegradable biopolymer-based alternatives. Thus, in current study, electrospun fish gelatin mats were fabricated by adding essential oils (EOs) namely, cinnamaldehyde (CEO), limonene (LEO), and eugenol (EEO) at 1, 3 and 5% with β-cyclodextrins (βCD) at an equimolar ratio. All the mats showed defect-free cylindrical morphology of fibers with a diameter ranging from 315 to 480 nm. Fourier transform infrared spectroscopy (FTIR) revealed no change in the chemical structure of gelatin after electrospinning. Nevertheless, reduced tensile strength (TS) and elongation-at-break (EAB) were observed for mats with EOs/βCD. The gelatin mats with EOs/βCD complexes showed improved melting temperature (Tm) with a rise of 3 to 13 °C. The highest radical scavenging activity (96.5%) was obtained by mats with EEO, while mats with CEO outperformed in antibacterial activity with the highest inhibition zone of 27.73 mm. The mats with all three EOs showed similar antifungal activity at 5% concentration. The mats presented good functional stability and a slow release of EOs for 60 days at ambient temperature. Thus, the results of the study indicate the suitability of the developed gelatin mats for possible application as active antimicrobial food packaging.